Análise da eficiência dos gastos públicos nos institutos federais: o caso do Instituto Federal de Educação, Ciência e Tecnologia de Sergipe - Matos, Graziana OLinda da Silva (2020)
The public resources used in public policy projects generate important results for society. In this sense, this research seeks to portray whether the Federal Institutes, which are a public policy project in education, are efficient in the use of public resources made available in their budgets. This efficiency will be measured through the Data Envelopment Analysis - DEA together with the Malmquist Productivity Index. As a reference, the investigation of the Federal Institute of Education, Science and Technology of Sergipe was emphasized. The Institutes have their creation dated at the end of 2008 when the Federal Education Centers and the Agrotechnical Schools merged, giving rise to the model that is found today throughout Brazil. Since then, a network expansion project has been put in place to serve the most diverse regions of the country. The Secretariat for Professional and Technological Education - SETEC is the administrative body that monitors and supervises the actions implemented by the Institutes. There is a set of twelve management indicators that serve for SETEC to monitor the results presented by each Institute, in compliance with a determination of the Federal Court of Accounts. These indicators will be the data used in the research to analyze the efficiency of expenses. The data are released annually through a report that measures and evaluates the results of the indicators, which are currently reported through the Nilo Peçanha Platform. The years 2015 to 2018 will be analyzed, as these are the standardized reports made available by SETEC with complete and more reliable information to what actually occurred in all the units analyzed. As a result, it was found that almost half of the institutions analyzed did not reach full efficiency in the years of the analysis, including the IFS. However, in two years of the series analyzed, the Institution came very close to the efficiency frontier. The full use of the Nilo Peçanha Platform from the year 2017 has substantially improved the collection and collection of data from the Network. Another important finding was the non-evolution in technological change throughout the Network over the years analyzed, which may be a proposal for future research.